Effect of Gamma Rays, EMS, DES and COH on Protein and Oil Content in Soybean - D. Dhanavel*, P. Pavadai, M. Girija and (Journal of Ecobiotechnology, 2010)
<table class="MsoNormalTable" style="border-collapse: collapse; mso-border-top-alt: solid black 1.5pt; mso-padding-alt: 0in 5.4pt 0in 5.4pt; mso-border-bottom-alt: solid black 1.5pt; mso-yfti-tbllook: 1184;" border="1" cellspacing="0" cellpadding="0"> <td style="border-right: #d4d0c8; padding-right: 5.4pt; border-top: black 1.5pt solid; padding-left: 5.4pt; padding-bottom: 0in; border-left: #d4d0c8; width: 349.25pt; padding-top: 0in; border-bottom: black 1pt solid; background-color: transparent; mso-border-top-alt: solid black 1.5pt; mso-border-bottom-alt: solid black .75pt;" width="466" valign="top"> Abstract The present study is based on the observations of seed protein and oil content in four mutagenic generations of soybean variety CO 1. Ethyl methane sulphonate treatment showed high protein and oil content compared to other mutagenic treatments such as gamma rays, diethyl sulphate and colchicine. Both increased and decreased content of protein and oil were observed. According to our results high content of protein and oil was observed at high mutagenic treatments. Increased level of seed protein and oil content was observed at 0.5% and 0.6% of EMS treatments and 50 KR of gamma rays. Department of Botany, Annamalai University, Annamalai Nagar – 608 002, Tamil Nadu, India — Please Cite This Article As: P. Pavadai, M. Girija and D. Dhanavel. 2010. Effect of Gamma Rays, EMS, DES and COH on Protein and Oil Content in Soybean. J. Exp. Sci. 2(4):47-50.